Glucagon-like peptide-1 receptor agonist-induced cholecystitis and cholelithiasis: a real-world pharmacovigilance analysis using the FAERS database - Tao, Chao; Zhang, Yinhui; Wan, Tenggang; Zhao, Wenting; Chen, Jing; Wang, Ke; Yang, Liuxuan; Wang, Guojun; Ding, Qian; Shang, Jinlu; Zhou, Meiling (Frontiers in Pharmacology, 2025)
BackgroundWith the widespread use of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in managing diabetes and obesity, the occurrence of GLP-1 RA-induced cholecystitis and cholelithiasis has raised increasing concern among healthcare professionals.MethodsThis study extracted adverse event reports of GLP-1 RA-induced cholecystitis and cholelithiasis from the FDA Adverse Event Reporting System database, covering Q1 2004 to Q2 2024. Disproportionality analysis methods, including the reporting odds ratio, proportional reporting ratio, and Bayesian confidence propagation neural network, were employed to identify associations between GLP-1 RAs and these AEs. The analysis focused on the five most commonly prescribed GLP-1 RAs, evaluated at both high-level term and preferred term levels.ResultsA total of 1,829 reports were identified in which GLP-1 RAs were listed as the primary suspect drug, involving 1,651 patients. All three signal detection methods indicated a positive signal between GLP-1 RAs and these conditions. The majority of cases occurred in patients aged 45 years and older, with a significantly higher prevalence in females. The median onset time of GLP-1 RA-induced cholecystitis and cholelithiasis was 182 days, with variations observed across different drugs, genders, and age groups.ConclusionThis study provides a comprehensive pharmacovigilance analysis of GLP-1 RA-induced cholecystitis and cholelithiasis, offering valuable insights into the prevention and management of these AEs.